Modification of the ESAW culture medium used for cultivation of marine diatoms - Polyakova, S. L.; Davidovich, O. I.; Podunay, Yu. A.; Davidovich, N. A. (Marine Biological Journal, 2018)
Experiments with clonal cultures of four pennate diatoms Haslea karadagensis, H. ostrearia, Pleurosigma sp. and Pseudo-nitzschia cf. seriata revealed that adding of sodium thiosulfate to the culture medium resulted in increase of algae growth rate. The highest, approximately two-fold, increase of the growth rate was observed in Pseudo-nitzschia cf. seriata, a member of the genus including toxicogenous species. Dependence of the algae growth rate on concentration of sodium thiosulfate was studied; optimal concentrations providing the highest growth rate were determined. Addition of ferrous-ammonium citrate or replacement of ferric chloride with ferrous-ammonium citrate did not affect the growth rate of the diatoms studied. For practical reasons, it is useful to prepare culture medium with the salinity of 36 ‰. Modified recipe of the ESAW medium is given.